Sustainability Implementation of UI Green Metric World University Rankings Energy & Climate Change (EC) Indicators: A Case Study of MUET Gymnasium Fitness Facility - Arsal Mehmood; Toussef Ali Shahani; Murtaza Ali Khuharo (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2021)
Mehran University of Engineering & Technology is a public university established in 1973. Wit seventeen faculties of multi-disciplines and having more than 7,500 students, MUET has made lots of achievements. In 2019, MUET is ranked 271 in the world, 2nd in Pakistan, 1st in Sindh Province, and slotted 275th in terms of Energy and Climate change (EC) indicators implementations on Sustainable development by UI GreenMetric World University Rankings. UI GreenMetric is a sustainability-based ranking whose aim is to provide rankings of universities all over the world based on their efforts for the implementation of pre-define indicator criteria. One of the criteria for this ranking is the Energy and Climate change (EC) indicator which had a most 21 percent weightage. In this review, this paper presents a detailed analysis for the implementation of EC indicators of UI GreenMetric World University Rankings to reduce carbon dioxide footprints and maintain sustainability at MUET gymnasium fitness facility. In this mechanism, an Energy Efficient Flywheel-Based KERS (Kinetic Energy Recovery System) Bicycle Generator is designed and developed. Additionally, a techno-economic (Energy, Cost and Co2 emission saving) beneficial analysis of generators with their usage as a free renewable energy source to overcome luminosity demand of MUET gymnasium fitness facility by an efficient LED lighting system and their relative relation with the EC indicator implementation is also discussed.